Passion fish [videorecording (DVD)] - McDonnell, Mary; Woodard, Alfre, 1953-; Burmester, Leo, 1944-2007; Curtis-Hall, Vondie; Sayles, John, 1950-; Sayles, John, 1950-; Sayles, John, 1950- (Columbia Tristar Home Video, 1998)
After an auto accident leaves her paralyzed, ex-soap opera star May-Alice Culhane returns to her now-empty family home in the bayous of Louisiana where she proceeds to drive away a succession of nurses-- until Chantelle. May-Alice and Chantelle form an unlikely friendship, and explore the bayou, as well as the murkier aspects of men, romance, and family.